Miniaturized microdosimeters as LET monitors: First comparison of calculated and experimental data performed at the 62 MeV/u 12C beam of INFN-LNS with four different detectors - Colautti, P; Conte, V; Selva, A; Chiriotti, S; Pola, A; Bortot, D; Fazzi, A; Agosteo, S; Treccani, M; De Nardo, L; Verona, C; Rinati, G Verona; et al. (Physica medica, 2018)
PURPOSE: The aim of this paper is to investigate the limits of LET monitoring of therapeutic carbon ion beams with miniaturized microdosimetric detectors. METHODS: Four different miniaturized microdosimeters have been used at the 62 MeV/u 12C beam of INFN Southern National Laboratory (LNS) of Catania for this purpose, i.e. a mini-TEPC and a GEM-microdosimeter, both filled with propane gas, and a silicon and a diamond microdosimeter. The y-D (dose-mean lineal energy) values, measured at different depths in a PMMA phantom, have been compared withLET¯D (dose-mean LET) values in water, calculated at the same water-equivalent depth with a Monte Carlo simulation setup based on the GEANT4 toolkit. RESULTS: In these first measurements, no detector was found to be significantly better than the others as a LET monitor. The y-D relative standard deviation has been assessed to be 13% for all the detectors. On average, the ratio between y-D and LET¯D values is 0.9 ± 0.3, spanning from 0.73 ± 0.08 (in the proximal edge and Bragg peak region) to 1.1 ± 0.3 at the distal edge. CONCLUSIONS: All the four microdosimeters are able to monitor the dose-mean LET with the 11% precision up to the distal edge. In the distal edge region, the ratio of y-D to LET¯D changes. Such variability is possibly due to a dependence of the detector response on depth, since the particle mean-path length inside the detectors can vary, especially in the distal edge region.
Keywords: Equipment Design; Miniaturization; izotopy uhlíku; počítačová simulace; Radiometry; fantomy radiodiagnostické; polymethylmethakrylát; Carbon Isotopes; Monte Carlo Method; Calibration; celková dávka radioterapie; radiometrie; radioterapie těžkými ionty; Computer Simulation; voda; kalibrace; miniaturizace; Water; metoda Monte Carlo; Heavy Ion Radiotherapy; Phantoms, Imaging; Polymethyl Methacrylate; Radiotherapy Dosage; design vybavení